Radiofluorescence of quartz from rocks and sediments and its correlation with thermoluminescence and optically stimulated luminescence sensitivities - Niyonzima, P.; Sawakuchi, A. O.; Jain, M.; Kumar, R.; Mineli, T. D.; Del Río, I.; Pupim, F. (Ancient TL, 2020)
The present study examines radiofluorescence (RF) emissions in quartz from parent rocks (igneous plutonic and volcanic) and sediments of different provenances, which represent a range of optically stimulated luminescence (OSL) and thermoluminescence (TL) sensitivities observed in nature. OSL and TL (110 °C peak) sensitivities of quartz have been successfully used for sediment provenance analysis, but the considerable sensitivity variations are still poorly understood in terms of charge traps and recombination centers. In the studied samples, the RF spectra obtained at room temperature and using X-ray irradiation consist of two broad emission bands: the first emission band is centered at ∼ 1.9 eV (blue) and has a higher intensity compared to the second emission band centered at ∼ 3.5 eV (ultraviolet, UV). The deconvolution analysis confirms that the quartz RF spectrum is at least the sum of four emission bands located between 1.5 eV (827 nm) and 4.0 eV (310 nm). The general observation is that the RF intensity differs between quartz from rocks and sediments, and among quartz from sediments with different provenances. Generally, quartz from sediments showed higher RF intensity compared to quartz from rocks, rendering the same pattern observed for OSL and TL sensitivities. For quartz from sediments, we observed strong correlations between the UV-RF band intensity and the OSL or 110 °C TL sensitivities. We argue that these correlations may be attributed to the fact that both 110 °C TL peak and OSL of quartz use the same recombination centers rather than the same electron trap. The UV-RF intensity measured using X-ray sources can also be used for provenance analysis of sediments in the same way as the OSL and TL sensitivities.